Vacuum deposition of high performance gas barrier materials - Suttle, H; Topping, A; Assender, H (2008)
High performance flexible barrier films produced by roll-to-roll processing are required for applications such as OLEDs, PVs and transistors. This paper presents the development of barrier layer technology for electronics applications on our vacuum web coating research facility. There is a capability of organic and inorganic layer deposition, with this paper focusing particularly on DC and RF sputtering onto acrylate smoothed substrates.